Efecto del lactosuero, como suplemento en la alimentación de pollos broilers, en la etapa de inicio, suministrada en forma líquida, en tres concentraciones: 10%, 15% y 20%, en el agua de bebida - Upiachihua Cardenas, Miler (2011)
The following research consisted of 500 broiler chickens were distributed in four treatments with two repetitions, only in the initial stage (0 - 3 weeks). The study was done to determine the effect of lactosuero as a supplement in feeding for broiler chickens, supplied in liquid form, in three concentrations (10%, 15% and 20%). The lactosuero was applied as a supplement in the drinking water, mixing it daily with water treatments (T1: 10%) (T2: 15%) (T3: 20%) in a ratio of (1:9 ie 1 L of lactosuero per 9 L of water) (1.5:8.5 ie 1.5 L of lactosuero per 8.5 L of water) (2:8 or 2 L of lactosuero per 8 L of water). The control treatment was given water and B complex in intensive farming. As for the Power System in the control treatment (T0), food was traditional, that is, with all the inputs required for breeding and in treatments (T1, T2 and T3), the food was not added fishmeal, that provided the lactosuero is supplied with water, the food was given them daily, worth mentioning that the lactosuero that was given to the chickens was fresh, which was collected daily from the company DANE. The parameters evaluated were: water consumption, feed conversion and economic profitability. According the results were determined that the treatments (T1 and T2) had a positive effect of lactosuero as a food supplement, so that is a new alternative for poultry farmers, this input lowers production costs and of course increases the utility.